Transcranial Magnetic Stimulation in Tremor Syndromes: Pathophysiologic Insights and Therapeutic Role - Frey, Jessica; Hess, Christopher W.; Kugler, Liam; Wajid, Manahil; Wagle Shukla, Aparna (Frontiers in Neurology, 2021)
Transcranial magnetic stimulation (TMS) is a painless, non-invasive, and established brain stimulation technique to investigate human brain function. Over the last three decades, TMS has shed insight into the pathophysiology of many neurological disorders. Tremor is an involuntary, rhythmic oscillatory movement disorder commonly related to pathological oscillations propagated via the cerebello-thalamo-cortical pathway. Although tremor is the most common movement disorder and recent imaging studies have enhanced our understanding of the critical pathogenic networks, the underlying pathophysiology of different tremor syndromes is complex and still not fully understood. TMS has been used as a tool to further our understanding of tremor pathophysiology. In addition, repetitive TMS (rTMS) that can modulate brain functions through plasticity effects has been targeted to the tremor network to gain potential therapeutic benefits. However, evidence is available for only a few studies that included small patient samples with limited clinical follow-up. This review aims to discuss the role of TMS in advancing the pathophysiological understanding as well as emerging applications of rTMS for treating individual tremor syndromes. The review will focus on essential tremor, Parkinson's disease tremor, dystonic tremor syndrome, orthostatic tremor, and functional tremor.